2020
DOI: 10.1371/journal.pone.0239987
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community analysis on the different mucosal immune inductive sites of gastrointestinal tract in Bactrian camels

Abstract: The microbial communities colonize the mucosal immune inductive sites could be captured by hosts, which could initiate the mucosal immune responses. The aggregated lymphoid nodule area (ALNA) and the ileal Payer's patches (PPs) in Bactrian camels are both the mucosal immune inductive sites of the gastrointestinal tract. Here, the bacteria community associated with the ALNA and ileal PPs were analyzed using of 16S rDNA-Illumina Miseq sequencing. The mutual dominant bacterial phyla at the two sites were the Bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…The intestinal immune system often nourishes prosperous bacterial communities and establishes advanced symbiotic relationships ( Sutherland & Fagarasan, 2012 ). Firmicutes, Bacteroidetes, and Proteobacteria were the three main phyla across all the samples in this study, which is consistent with our previous study that found that these phyla dominantly colonized on the surface of the different mucosal immune inductive sites of the gastrointestinal tract in Bactrian camels ( Zhang et al, 2020 ). Proteobacteria is conducive to the homeostasis of the anaerobic environment of the GI tract gut ( Moon et al, 2018 ), while the ratio of Firmicutes and Bacteroidetes impacts gut dysbiosis ( Grigor’eva, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The intestinal immune system often nourishes prosperous bacterial communities and establishes advanced symbiotic relationships ( Sutherland & Fagarasan, 2012 ). Firmicutes, Bacteroidetes, and Proteobacteria were the three main phyla across all the samples in this study, which is consistent with our previous study that found that these phyla dominantly colonized on the surface of the different mucosal immune inductive sites of the gastrointestinal tract in Bactrian camels ( Zhang et al, 2020 ). Proteobacteria is conducive to the homeostasis of the anaerobic environment of the GI tract gut ( Moon et al, 2018 ), while the ratio of Firmicutes and Bacteroidetes impacts gut dysbiosis ( Grigor’eva, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Recently, more research has been devoted to revealing the internal interactions between gut taxa and intestinal mucosa. By comparing commensal microbial composition differences between the aggregated lymphoid nodule area (ALNA) and the ileal PPS, we previously observed that the host’s intestinal microenvironment is selective for the symbiotic bacteria colonizing the corresponding sites, which could impact the physiological functions of the site ( Zhang et al, 2020 ). However, it is still unknown if there are associations between colonized flora and the gut-expressed genes in PPS.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we found the bacterial communities to be similar between the RMFR and LMFR (50). The similar bacterial structure suggests that these differences may not be caused by bacterial parasitism, but rather to the host's internal expression, which implies distinct physiological patterns for RMFR and LMFR.…”
Section: Discussionmentioning
confidence: 71%
“…In our previous study, we found the bacterial communities to be similar between the RMFR and LMFR [ 54 ]. The similar bacterial structure suggests that these differences may not be caused by bacterial parasitism, but rather to the host’s internal expression, which implies distinct physiological patterns for RMFR and LMFR.…”
Section: Discussionmentioning
confidence: 93%